How Do Perceptions of Risk Communicator Attributes Affect Emergency Response? An Examination of a Water Contamination Emergency in Boston, USA. Issue 1 (18th January 2022) - Hyman, Amy; Arlikatti, Sudha; Huang, Shih‐Kai; Lindell, Michael K.; Mumpower, Jeryl; Prater, Carla S.; Wu, Hao‐Che
Abstract: A water main break that contaminated the Boston area's water distribution system prompted a four‐day "boil water" order. To understand risk communication during this incident, 600 randomly sampled residents were mailed questionnaires, yielding 110 valid responses. This article describes how perceptions of different social stakeholders influenced whether respondents complied with the Protective Action Recommendation—PAR (i.e., drank boiled water), took alternative protective actions (i.e., drank bottled water or/and self‐chlorinated water), or ignored the threat (i.e., continued to drink untreated tap water). Respondents perceived technical authorities (i.e., water utility, public health, and emergency management) to be higher on three social influence attributes (hazard expertize, trustworthiness, and protection responsibility) than public (i.e., news media, elected officials) and private (i.e., self/family, peers, and personal physicians) intermediate sources. Furthermore, respondents were most likely to comply with the PAR if they perceived authorities and public intermediates to be high on all three attributes and if they had larger households and lower income. Contrarily, they were more likely to take alternative actions if they were younger and had higher levels of income, risk perception, and emergency preparedness. These results underscore the need for technical authorities to develop credibility with their potential audiences before a crisis occurs. Key Points: People perceived different authorities' credibility similarly, underscoring the need for them to provide compatible warning messaging Planning with multiple stakeholders and citizens before an incident is important to increase awareness and protective action compliance Water safety management must be integrated with a community's comprehensive emergency operations planning to ensure effective response